Seroprevalence survey of chikungunya virus in Bagan Panchor, Malaysia - Ayu, S.M.; Lai, L.R.; Chan, Y.F.; Hatim, A.; Hairi, N.N.; Ayob, A.; Sam, I.C. (2010)
In 2006, an outbreak of Chikungunya virus (CHIKV) of the Asian genotype affected over 200 people in Bagan Panchor village in Malaysia. One year later, a post-outbreak survey was performed to determine attack rate, asymptomatic rate, and post-infection sequelae. Findings were compared with recent CHIKV outbreaks of the Central/East African genotype. A total of 180 residents were interviewed for acute symptoms and post-infection physical quality of life and depressive symptoms. Sera from 72 residents were tested for CHIKV neutralizing antibodies. The estimated attack rate was 55.6, and 17.5 of infected residents were asymptomatic. Arthralgia was reported up to 3 months after infection, but there were no reports of long-term functional dependence or depression. Symptomatic and seropositive residents were significantly more likely to live in the area with the most dense housing and commercial activities. CHIKV had a high attack rate and considerable clinical impact during the Bagan Panchor outbreak.